A modular approach to real-time cork classification using image processing - Lima, José (2010)
This paper’s main purpose is to present an automatic vision assortment system for cork classification. Cork is a natural material that is used to seal wine bottles for its reliability and for its chemical and mechanic properties. A modular approach isolates the hard real-time sub problems. It includes some custom developed hardware and software. The developed and implemented system acquires images by a linear CCD camera, transmits that image over an Ethernet based network and processes that image to extract quantitative elements. This system can analyse and distinguish defects that one can find on the surface of a cork stopper and it is also possible to adapt the system to other kinds of problems. The size, form and position of the defects are analysed and the stability of repeated measures is observed. This result allows us to validate the presented methodology.